Analisis Lama Penyimpanan Kemplang Ikan Palembang yang Diproses dengan Panas dari Gelombang Mikro dan yang Digoreng - Meriska Indriani; Filli Pratama; Hermanto Hermanto (Jurnal FishtecH, 2019)
Palembang fish crackers have a thick characteristic with a strong fishy aroma. Puffing of the thick fish cracker requires particular technique, for example the deep-frying techniques should use two different heating temperatures to obtain good quality of crackers. Another alternative method is to use heat from microwaves. One of the disadvantages of crackers that are processed with heat from the microwave is the easiness of the crackers lose its crispness. This study aimed to analyze the shelf-life of fish crackers puffed by microwave heat and deep-frying technique in some types of packaging. The research design was a factorial completely randomized design with two factors namely the type of packaging (polypropylene, nylon, metalized plastic) and type of crackers (microwaved and fried). Analysis of variance showed that all treatments have a significant effect on water content.  The indicator used for the prediction of shelf-life is water content. The water content changes during storage at room temperature for all treatments followed a first-order kinetic with the lowest k value for fish cracker packed in metalized plastic packaging with 57 days storage time (microwavable fish crackers) and 45 days (fried fish crackers)